(untitled) (GEON Journal (Management, Organizations and Business), 2021)
Problem: The need for an intra-regional analysis of the North-Central region of Mexico, as the region with the highest economic growth in the country, to answer the research question: how are the states of the North-Central region of Mexico distributing their economic activities? Objectives: to carry out an intra-regional analysis to know how the states of the North Central region of Mexico distribute their economic activities and the way in which they use their resources. Materials and methods: Intraregional analysis techniques were used for the development of the research. The first was the location coefficient to evaluate the level of concentration of the sectors of the region’s economy; the second technique is the territorial association coefficient, which helps to make comparisons from the perspective of geographic distribution. Results: The main results in the region in terms of concentration within the economy in the period 2015-2019 are shown, in addition to the existing disparities in terms of territorial association in that period. Discussion: the research highlights the need for the analysis of disparities at the territorial level and the need for the use of local government analysis tool, as well as the importance of applying regional analysis techniques in the evaluation of territories. Conclusions: Intra-regional analysis techniques represent an essential instrument in the diagnosis and evaluation of the states of the Mexican Republic and can be applied to different indicators that allow improving the analysis of the situation of each territory. Contribution / originality: The contribution of the research lies in obtaining the description of the behavior of the gross value added of the primary, secondary and tertiary sectors of the North Central region of Mexico. In addition, from the calculation of coefficients it is possible to analyze the concentration of economic activities in the region.